Kontribusi CAR, NPL, LDR, BOPO, DAN NIM terhadap Return On Asset Bank Pembangunan Daerah - Ramadhan, Yanuar; Rosadi, Rizky Meydina Viersha (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Current economic development cannot be separated from the banking sector, the role of banks in advancing a country's economy is very large. Then the world was shocked by the phenomenon of the Covid-19 pandemic which caused restrictions on community activities so that it affected business activities which resulted in affecting the growth and stability of the economy. The Central Statistics Agency report in 2019 was 5.07% and BPS in 2020 was 2.97%, so BPS said the Indonesian economy shrank 2.1%. After recovery from the Covid-19 pandemic in 2021, the Indonesian economy experienced increased growth of 3.69%. Several things can be seen from the performance report to be able to improve its performance, one indicator that needs to be paid attention to is Return On Assets because this ratio can be used to determine whether the company is effective in gaining overall profits. This research aims to test and compare CAR, NPL, LDR, BOPO, and NIM against ROA from regional development bank financial performance reports for the 2017-2022 period. This research uses 23 Regional Development Bank samples from 2017-2022. This research uses a purposive sampling technique and uses the hypothesis method of multiple linear regression analysis to analyze panel data using Eviews 10 software. The research results show that the variables CAR, NPL, LDR, BOPO, NIM have a simultaneous effect on ROA growth. Loan to Deposit Ratio and Net Interest Margin have a significant influence on Return On Assets. Meanwhile, the Capital Adequency Ratio, Non-Performing Loans, and operational costs and operational income do not have a significant effect on Return on Assets at Regional Development Banks for the 2017-2022 period.